BRIDGING TECHNOLOGY MANAGEMENT WITH DYNAMIC CAPABILITIES FOR SUSTAINABLE COMPETITIVE ADVANTAGE (Journal of Technology and Operations Management, 2017)
This article attempts to explain the concept of technology management (MOT) for sustaining competitive advantage. To better understand how sustainable competitive advantage can be created with MOT, the concept of dynamic capabilities (DCs) that is designed to respond to technological change is brought into the picture. With DCs, this article has characterized MOT’s activities and routines as firm’s internal and intangible resources that are specific and identifiable with common features, but idiosyncratic in details. With these characteristics, MOT can be unique, difficult to imitate, rare, and valuable to explain the source of sustainable competitive advantage. To achieve this objective, a framework that serves as a basis to table the linkages between MOT and DCs is proposed. With the framework, it becomes clear where DCs’ micro-foundations of opportunity sensing, opportunity seizing, and resource transformation can be bridged directly to the existing MOT’s activities and routines. Although DCs’ micro-foundations, and MOT’s activities and routines are adopted directly from the existing literature, this article has managed to clearly defined where the specific MOT’s activities and routines are linked to the specific DCs’ micro-foundations. As a result, the nature of MOT as a DCs’ tool for sustaining competitive advantage has been understood. For future studies, the framework serves as a guideline to systematically investigate the linkages between MOT and DCs.